Affective context interferes with brain responses during cognitive processing in borderline personality disorder: fMRI evidence. Issue 1 (30th July 2015) - Soloff, Paul H.; White, Richard; Omari, Amro; Ramaseshan, Karthik; Diwadkar, Vaibhav A.
Abstract: Emotion dysregulation in borderline personality disorder (BPD) is associated with loss of cognitive control in the face of intense negative emotion. Negative emotional context may interfere with cognitive processing through the dysmodulation of brain regions involved in regulation of emotion, impulse control, executive function and memory. Structural and metabolic brain abnormalities have been reported in these regions in BPD. Using novel fMRI protocols, we investigated the neural basis of negative affective interference with cognitive processing targeting these regions. Attention-driven Go No-Go and X-CPT (continuous performance test) protocols, using positive, negative and neutral Ekman faces, targeted the orbital frontal cortex (OFC) and the anterior cingulate cortex (ACC), respectively. A stimulus-driven Episodic Memory task, using images from the International Affective Pictures System, targeted the hippocampus (HIP). Participants comprised 23 women with BPD, who were compared with 15 healthy controls. When Negative>Positive faces were compared in the Go No-Go task, BPD subjects had hyper-activation relative to controls in areas reflecting task-relevant processing: the superior parietal/precuneus and the basal ganglia. Decreased activation was also noted in the OFC, and increased activation in the amygdala (AMY). In the X-CPT, BPD subjects again showed hyper-activation in task-relevant areas: the superior parietal/precuneus and the ACC. In the stimulus-driven Episodic Memory task, BPD subjects had decreased activation relative to controls in the HIP, ACC, superior parietal/precuneus, and dorsal prefrontal cortex (dPFC) (for encoding), and the ACC, dPFC, and HIP for retrieval of Negative>Positive pictures, reflecting impairment of task-relevant functions. Negative affective interference with cognitive processing in BPD differs from that in healthy controls and is associated with functional abnormalities in brain networks reported to have structural or metabolic abnormalities. Task demands exert a differential effect on the cognitive response to negative emotion in BPD compared with control subjects. Highlights: Negative affective interference is associated with functional abnormalities in brain networks. Emotion dysregulation may be mediated by effects of negative emotion on vulnerable brain networks. The "top down/bottom up" model is insufficient to explain all of the effects of negative emotion. Affective interference is driven, in part, by the stimulus- or attention-driven dynamics of the task.